2005
DOI: 10.1159/000087286
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic-Acid-Induced Circulating Level Modifications of Angiogenic Factors, Metalloproteinases and Proinflammatory Cytokines in Metastatic Breast Cancer Patients

Abstract: Background: To evaluate the modifications of circulating angiogenic factors, metalloproteinases and acute-phase cytokines after the first single zoledronic acid (ZA) intravenous infusion. Experimental Design:Eighteen consecutive breast cancer patients with bone metastases were evaluated for circulating levels of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), metalloproteinase 1 (MMP-1), metalloproteinase 2 (MMP-2), interleukins 1β, 6 and 8 (IL-1β, IL-6, IL-8), interferon γ, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 59 publications
4
73
3
3
Order By: Relevance
“…About the use of zoledronic acid in solid tumor, Santini et al [4] reported that in patients with advanced solid cancer and bone metastasis, pamidronate [2] and zoledronic acid [4][5][6][7][8][9][10][11][12][13] showed antiangiogenic properties which were associated with a significant and long-lasting decrease of VEGF serum levels following bisphosphonates infusion. These observations were later confirmed by Ferretti et al [14] who observed a transient but significant reduction of VEGF and bFGF, 48 hours after the infusion of zoledronic acid in breast cancer patients with bone metastasis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…About the use of zoledronic acid in solid tumor, Santini et al [4] reported that in patients with advanced solid cancer and bone metastasis, pamidronate [2] and zoledronic acid [4][5][6][7][8][9][10][11][12][13] showed antiangiogenic properties which were associated with a significant and long-lasting decrease of VEGF serum levels following bisphosphonates infusion. These observations were later confirmed by Ferretti et al [14] who observed a transient but significant reduction of VEGF and bFGF, 48 hours after the infusion of zoledronic acid in breast cancer patients with bone metastasis.…”
Section: Discussionsupporting
confidence: 58%
“…We reported different hypothetical mechanism of anti-MM activity of zoledronic acid, for which there is actually no consensus, for this reason, according with the results found in solid tumors, we explored the contribution of bisphosphonates in anti-MM activity studying its potential anti-angiogenic effect based on modification of cytokines which are pivotal in this pathogenic mechanism [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…46 Moreover, zoledronate displays antiangiogenic activity and can decrease the secretion of immunosuppressive (TGF-b, FGF-b and metalloproteinases) and proinflammatory (IL-1b, IL-6 and IL-8) factors. 42,[47][48][49][50] In a previous clinical trial designed to evaluate phosphoantigen administration in B-cell malignancies, a correlation was observed between the in vivo expansion of Vc9Vd2 T cells and the objective antitumor response. 18 An adoptive transfer immunotherapy assay has also been conducted in metastatic renal cell carcinoma by Kobayashi et al 21 and in lung carcinoma by Nakajima et al 51 These studies found that autologous Vc9Vd2 T cells are well tolerated and induce an antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…(Original magnification x10, x40 and x100) expression by infiltrating macrophages and inhibited MMP-9 activity by reducing association of VEGF with its receptor on angiogenic endothelial cells in a mouse model of human cervical carcinogenesis. Additionally, ZA treatment was shown to decrease circulating levels of MMP-2, VEGF and basic fibroblast growth factor (bFGF) in metastatic breast cancer patients (38). Furthermore, alendronate which is another bisphosphonate was exerted to reduce the secretion of MMP-2 and MMP-9 by metastatic PC-3 ML cells in mice (39).…”
Section: Discussionmentioning
confidence: 99%